Structural design and optimization of double-cross shape broadband absorption metamaterial based on CB-ABS - Chen, Mengzhou; Wang, Liuying; Liu, Gu; Ge, Chaoqun; Wang, Long; Xu, Kejun; Wang, Weichao (Frontiers in Materials, 2022)
This work presents a novel broadband double-cross shape metamaterial structure based on the Carbon Black-Acrylonitrile-Butadiene-Styrene (CB-ABS) composite material. The optimal metamaterial structure with the thickness of 7 mm shows a broadband absorption characteristic in the frequency range of 5.1–40 GHz. Additionally, the low volume filling fraction of the proposed metamaterial structure will be helpful to achieve lightweight broadband absorption performance. Meanwhile, the metamaterial structure can also display a wide-angle absorption performance from 0° to 55° for TE mode and 0°–75° for TM mode. Moreover, this research provides an effective and promising way for the practical application of the lightweight broadband and wide-angle microwave strong absorption metamaterial in the future.